2009
DOI: 10.1177/0961203308097473
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine –Induced Hair Depigmentation

Abstract: A case of hair depigmentation induced by chloroquine diphosphate subacute overdosage in an 11-year-old patient with dermatomyositis is presented. Normal coloured hair growth occurred after normalisation of chloroquine dosage. A discussion on possible pathomechanisms of this phenomenon is made based on experimental data and previously reported patients with the same condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…This hypothesis is consistent with the fact that the main known risk factor for these hyperpigmented macules is the taking of antiaggregant or anticoagulant treatment [115,116]. Concerning the depigmentation of integuments, mechanisms of 4-AQ-induced poliosis and vitiligo remain unclear; the main hypothesis is that 4-AQ bind to eumelanin and pheomelanin and so disturb melanogenesis [122].…”
Section: Mechanismssupporting
confidence: 68%
“…This hypothesis is consistent with the fact that the main known risk factor for these hyperpigmented macules is the taking of antiaggregant or anticoagulant treatment [115,116]. Concerning the depigmentation of integuments, mechanisms of 4-AQ-induced poliosis and vitiligo remain unclear; the main hypothesis is that 4-AQ bind to eumelanin and pheomelanin and so disturb melanogenesis [122].…”
Section: Mechanismssupporting
confidence: 68%
“…Chloroquine (CHL) is an antimalarial drug approved by both the Food and Drug Administration (FDA) and European Medicines Agency (EMA) for the treatment of lupus erythematosus and rheumatoid arthritis. Lightening on the hair scalp, and less frequently on the eyelashes, eyebrows, moustache and body hair, has been shown to be induced by CHL administered at a dosage starting from 250 mg daily [11][12][13][14][15][16][17][18][19][20][21][22][23]. Hair hypopigmentation (a brightening of any hair colour leading to whitening) occurred from four weeks up to 12 months after treatment initiation, and was reversible after discontinuation or dosage reduction.…”
Section: Drugs That Induce Hair Colour Changes Chloroquinementioning
confidence: 99%
“…The pathophysiological mechanism of hair and skin hypopigmentation during CHL treatment is not fully understood, but previous studies showed remarkable affinity of CHL for those tissues which have abundant melanin content, such as the skin and eyes [26]. Hypopigmentation was indeed more common in patients with blond, light brown, or red hair, suggesting a greater interaction between CHL and pheomelanin rather than eumelanin [21]. However, even subjects with darker hair may experience hair lightening [13,14,17].…”
Section: Drugs That Induce Hair Colour Changes Chloroquinementioning
confidence: 99%
“…Hair graying is associated with various autoimmune disorders including vitiligo and several rare premature aging syndromes including the Hutchinson Gilford and Werner'syndrome 7 . Hair graying may also reflect nutritional deficiencies (especially of vitamins) and the use of drugs such as chloroquine 8 9 10 . We do not know exactly the cause of hair graying in humans.…”
Section: Introductionmentioning
confidence: 99%